(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study was carried out to examine the impact of liquid organic fertilizer Ergonfill (LFE) on the yield and quality of cherry tomato (Lycopersicon esculentum Mill.Sakura F1) under different growth conditions. The experiment was set up in a randomized blocks design with four variants in three replications. Experiment variants were as follows: drought-stressed seedlings with and without LFE treatment, and non-stressed seedlings with and without LFE treatment. Exposure of cherry tomato seedlings to controlled water stress conditions significantly increased fruit quality parameters (total soluble solids, titratable acidity, ascorbic acid, lycopene, total phenolic and flavonoids, total antioxidant capacity), but decreased yield. LFE treatment significantly increased by the all examined parameters under normal growth conditions as compared to untreated plants, and for total phenolic and flavonoids content, total antioxidant capacity and total soluble solids this increase was statistically significant. Positive impact of the LFE application on cherry tomato quality is result of fertilizer composition, as well as ability of cherry tomato plants to use bioactive substances in fertilizer for its growth and development.